National documentation on the problems of arsenic and Farakka - International Conference on the Problem of Surface and Groundwater Management, Arsenic Contamination, and Desertification Syndrome in Bangladesh (1998 : Dhaka, Bangladesh); Ahmad, Jasim Uddina; International Farakka Committee (New York, U.S.A.); International Conference on Farakka Barrage (1993 : New York, N.Y.) (New York : Mohammad Hossain Khan and Abu Syeed Shaheen on behalf of International Farakka Committee, 2003)
Contributed papers of International Conference on the Problems of Surface and Groundwater Management, Arsenic Contamination and Desertification Syndrome in Bangladesh; with reference to adverse effects of Farakka Barrage; abstracts of International Seminar on Farakka Barrage and one another seminar included.
Includes bibliographical references.
Keywords: Arsenic -- Toxicology -- Bangladesh -- Congresses